Practica académica calidad de producto y bienestar laboral, realizada en Busscar de Colombia S.A. (2011)
This text contains detailed information the process of practice organizational psychology conducted between December 2010 and September 2011 in Busscar de Colombia SA initially focused on the identification of needs which facilitated defining an axis of intervention priority for the organization: Developing and sustaining a culture of quality reflected in the commitment and attitude of employees. The diagnostic process was evident the need to build, nurture and focus the plan being of the company.